?VOLATILES OF OCIMUM BASILICUM (LOCAL) AT DIFFERENT PHASES OF PLANT GROWTH (Biological Sciences - PJSIR, 1999)
The essential oil of Ocimum basilicum (Local) (0.27-0.29%) obtained by hydrodistillation of the plant at various phases was characterised by GCIMS. Among the 22 compounds identified Linalool (83.0-87.1 %), 1:8 Cineole (3.2-4.7%) and Camphor (0.4-0.5%) predominated, while other constituents were either in small quantities or in traces.